2022
DOI: 10.9745/ghsp-d-21-00715
|View full text |Cite
|
Sign up to set email alerts
|

Health Policy and Systems Research Capacities in Ethiopia and Ghana: Findings From a Self-Assessment

Abstract: Government investment in strengthening health policy and systems research capacities is needed to enhance the generation of evidence for effective policy making. Researchers’ engagement in the policy-making process helps shape policy-relevant research and support policy-relevant decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…However, the practice of HPSR theme identification was not well exercised in most organizations. Studies from Ethiopia and Ghana showed that policymakers and research institutes voice that the level of HPSR spending is inadequate [ 29 ]. This is because researchers in different disciplines often work in isolation, in a fragmented, competitive, and highly specialized activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the practice of HPSR theme identification was not well exercised in most organizations. Studies from Ethiopia and Ghana showed that policymakers and research institutes voice that the level of HPSR spending is inadequate [ 29 ]. This is because researchers in different disciplines often work in isolation, in a fragmented, competitive, and highly specialized activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is now good evidence of how HPSR can address these issues (Strachan et al, 2022). Yet the capacity to undertake such research is limited in large parts of the world (Tangcharoensathien et al, 2022). The challenges involved should not, however, be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Obstacles to implementing this policy include the quantity of arable land, its fragmentation, the low irrigation productivity caused by low fertility soil, and the ownership issue with the land. However, the country's population is expected to increase by 2.5% annually, reaching 171.8 million by 2050, in this case, there will be a major demand-supply imbalance [23]. According to data, the size of the land restricts the mechanization of irrigation policy for roughly 38% of smallholder farmers and households, 23.6 percent have access to between 0.51 and 1.0 hectares, 24% have between 1 and 2 hectares, and 14. percent have more than 2 hectares of land [21].…”
Section: Constraints Of Irrigation Policy Achievement In Ethiopiamentioning
confidence: 99%